Design, synthesis and isolation of a new 1, 2, 5-selenadiazolidyl and structural and magnetic characterization of its alkali-metal salts. (8th October 2019) - Semenov, Nikolay A.; Radiush, Ekaterina A.; Chulanova, Elena A.; Slawin, Alexandra M. Z.; Woollins, J. Derek; Kadilenko, Evgeny M.; Bagryanskaya, Irina Yu.; Irtegova, Irina G.; Bogomyakov, Artem S.; Shundrin, Leonid A.; Gritsan, Nina P.; Zibarev, Andrey V.
Abstract : A new electron acceptor is synthesized and reduced into its radical-anion isolated in the form of two salts with different structures and magnetic properties. Abstract : 5, 6-Dicyano[1, 2, 5]selenadiazolo[3, 4- b ]pyrazine 1 was synthesized and electrochemically and chemically reduced into its radical anion [1 ]˙ −, which was characterized by EPR spectroscopy and DFT calculations, and isolated in the form of homospin salts [K(18-crown-6)] + [1 ]˙ − (2 ) and [Na(18-crown-6)] + [1 ]˙ − (3 ). The crystal structure of 2 revealed π-dimers of [1 ]˙ − featuring a shortened interplanar separation of 3.18 Å, and that of 3 showed chains of alternating cations and anions. DFT and CASSCF calculations on the π-dimers of [1 ]˙ − suggest a closed-shell singlet ground state with a noticeable contribution of diradical character. According to EPR and SQUID magnetometry, salt 2 is diamagnetic in the range of 2–300 K, whereas salt 3 is paramagnetic and reveals weak antiferromagnetic exchange interactions.